Monitoring Konsumsi Daya Listrik Menggunakan Google Spreadsheet - Zealita, Zarah; Prasetia, Vicky; Zaenurrohman (P3M Politeknik Negeri Cilacap, 2025)
The lack of detailed information on the daily electricity consumption of each electronic device can hinder the accurate calculation of electricity consumption costs. This can affect the accuracy and ease of access to electricity consumption data. This research aims to develop an electric power reading system using the PZEM-004T sensor, an electricity power monitoring system, and the cost of electricity usage through Google Sheets. The system is designed to measure current, voltage, power, and electricity costs with high accuracy. The test results show that the KWH meter reading system can measure electricity consumption using the PZEM-004T sensor with accuracy values of 99.805% for voltage (volts), 89.71% for current (amperes), and 99.98% for power (watts) in each test. The data from the sensor monitoring system and cost calculations can be effectively displayed on Google Sheets, which functions well for measuring and displaying data for current, voltage, power, and electricity billing.